Experiments With Surds & Exponentials…

\sqrt { a } \sqrt { a } ={ a }^{ \frac { 1 }{ 2 }  }{ a }^{ \frac { 1 }{ 2 }  }={ a }^{ \frac { 1 }{ 2 } +\frac { 1 }{ 2 }  }=a\\ \\ \sqrt [ 3 ]{ a } \sqrt [ 3 ]{ a } \sqrt [ 3 ]{ a } ={ a }^{ \frac { 1 }{ 3 }  }{ a }^{ \frac { 1 }{ 3 }  }{ a }^{ \frac { 1 }{ 3 }  }={ a }^{ \frac { 1 }{ 3 } +\frac { 1 }{ 3 } +\frac { 1 }{ 3 }  }=a\\ \\ \sqrt [ 4 ]{ a } \sqrt [ 4 ]{ a } \sqrt [ 4 ]{ a } \sqrt [ 4 ]{ a } ={ a }^{ \frac { 1 }{ 4 }  }{ a }^{ \frac { 1 }{ 4 }  }{ a }^{ \frac { 1 }{ 4 }  }{ a }^{ \frac { 1 }{ 4 }  }={ a }^{ \frac { 1 }{ 4 } +\frac { 1 }{ 4 } +\frac { 1 }{ 4 } +\frac { 1 }{ 4 }  }=a

\sqrt { \frac { a }{ b }  } \sqrt { \frac { a }{ b }  } ={ \left( \frac { a }{ b }  \right)  }^{ \frac { 1 }{ 2 }  }{ \left( \frac { a }{ b }  \right)  }^{ \frac { 1 }{ 2 }  }={ \left( \frac { a }{ b }  \right)  }^{ \frac { 1 }{ 2 } +\frac { 1 }{ 2 }  }=\frac { a }{ b } \\ \\ \sqrt [ 3 ]{ \frac { a }{ b }  } \sqrt [ 3 ]{ \frac { a }{ b }  } \sqrt [ 3 ]{ \frac { a }{ b }  } ={ \left( \frac { a }{ b }  \right)  }^{ \frac { 1 }{ 3 }  }{ \left( \frac { a }{ b }  \right)  }^{ \frac { 1 }{ 3 }  }{ \left( \frac { a }{ b }  \right)  }^{ \frac { 1 }{ 3 }  }={ \left( \frac { a }{ b }  \right)  }^{ \frac { 1 }{ 3 } +\frac { 1 }{ 3 } +\frac { 1 }{ 3 }  }=\frac { a }{ b }

{ a }^{ \frac { 1 }{ 2 }  }=b\\ \\ \therefore \quad a={ b }^{ 2 }\\ \\ { a }^{ \frac { 3 }{ 4 }  }=b\\ \\ \therefore \quad a={ b }^{ \frac { 4 }{ 3 }  }\\ \\ { a }^{ \sqrt { m }  }=b\\ \\ \therefore \quad a={ b }^{ \frac { 1 }{ \sqrt { m }  }  }\\ \\ \therefore \quad a={ b }^{ \frac { \sqrt { m }  }{ m }  }\\ \\ { a }^{ \frac { 1 }{ m+\sqrt { n }  }  }=b\\ \\ \therefore \quad a={ b }^{ m+\sqrt { n }  }

Other posts you may be interested in...